Insulation Properties of PMMA:TiO2 Nanodielectric Film for High Voltage Applications - Melvin Welan Mathew; Lyly Nyl Ismail; Norsabrina Sihab; Ahmad Asri Abd Samad; Nur Ashida Salim (Institute of Advanced Engineering and Science, 2018)
This research investigates the insulation properties of poly methyl methacrylate with titanium dioxide (PMMA:TiO2) nanodielectric film to be used as insulation layer in high voltage (HV) applications. AC and DC breakdown test has been conducted to investigate the insulation properties of PMMA:TiO2 nanodielectric to be used as solid insulation in HV. In this research, the PMMA:TiO2 nanodielectric film were prepared by varying the annealing temperature (60°C up to 180°C) and spin coating techniques wwere used to form the PMMA:TiO2 nanocomposite film. The insulation properties of the nanocomposite film were characterized using high voltage test (DC and AC breakdown strength) to identify which nanocompoiste film has the good insulation properties. In addition, different types of electrodes are also used to to measure the insulation properties of nanocompoiste film. The structural properties of PMMA:TiO2 nanocomposite films were characterized using atomic force microscopy (AFM). Results from HV test shows that the annealing temperature affected the insulation properties PMMA:TiO2 nanocomposite film. By increasing the annealing temperature, the insulation properties decreased. Film anneal at 120 oC has the good insulation compare to other temperature. 120 oC are the optimize temperature to prepared the PMMA:TiO2 nanocomposite films. Result from different types of electrodes show that sharp tip has high DC breakdown strength compare to spherical electrodes.